Local-Based Tourism Management and Challenges in Sustainable Destination Development in North Lombok Regency - Muhammad Yazid Khofi; Azis Meinudin (JURNAL ILMIAH DETUBUYA, 2026)
This study aims to analyze locally based tourism governance practices and identify challenges in developing sustainable tourism destinations in North Lombok Regency, West Nusa Tenggara. The study uses a qualitative case study design. Data were obtained through in-depth interviews with local government officials, tourism village managers, and local institutions, supported by documentary studies. Data analysis used thematic analysis to identify governance patterns, institutional dynamics, and factors influencing destination development. The results show that locally based tourism governance develops through the strengthening of community institutions, such as tourism awareness groups and village-owned enterprises, with the government acting as a facilitator and capacity builder for the community. However, governance implementation still faces various challenges, including policy fragmentation, weak coordination among institutions, limited local institutional capacity, limited fiscal support, dependence on external tourist flows, and disparities in destination development. The findings confirm that the success of sustainable destination development depends heavily on institutional capacity-building, policy integration, and stakeholder collaboration. This study contributes to the development of locally based tourism governance research and provides policy implications for more participatory and sustainable regional tourism management.